Le corps en Asie vu par Marco Polo - Dominique Boutet (Revue des Langues Romanes)
The question of the human body, its appearance and its uses is at the heart of Polo’s observation, as much as the economic details. After having examined in the encyclopedias, strongly marked by Pliny, the expectations of the Franco-Italian public of the beginning of the 14th century, we address the issue of physical otherness in the Devisement (for men and for their gods), emphasizing the importance of the destruction of the myths or at least of their decrease. We then study the uses and treatments of the body: as they strike against Western prohibitions, they are important markers of otherness. Finally, we study the “techniques of the body” (Marcel Mauss), the social practices which are the translation of the beliefs and the philosophy of life that Marco Polo also tries to report. We demonstrate this way that Marco Polo most often has a real ethnological look and that he tries to understand even more than to judge. For him, the treatments reserved for the human body make sense inside the whole of social life.